BIMBINGAN PRANIKAH SEBAGAI PENYADARAN FUNGSI SEORANG SUAMI BERDASARKAN MAZMUR 128:1-6 - Firman Panjaitan; Gary Reneker Bermula (POIMEN Jurnal Pastoral Konseling, 2022)
The purpose of marriage is to achieve a harmonious and happy family life. In reality, often domestic harmony and happiness do not materialize due to the misunderstanding of family members regarding their roles and functions in the family. Psalm 128:1-6 becomes an important part of the Bible which talks about the necessity of a man playing the role of a husband to build happiness in the family because it must be delivered at the time of premarital counseling. This study uses qualitative research with a literature study approach (Library Research), and specifically, in examining Psalm 128:1-6 the author uses a hermeneutic approach with the grammatical-historical approach to finding the meaning of the selected text. The findings in the study revealed that an understanding of the self-concept of a happy family that focuses on the role of a man as a husband must be built through premarital guidance. Therefore, premarital guidance is an absolute requirement to be carried out before entering into marriage.